Original paperThe estimation of erythropoietin levels in the blood serum and cystic fluid in patients with solitary renal cysts - Jabłonowski, Zbigniew; Rysz, Jacek; Paradowski, Marek; Miękoś, Eugeniusz; Różański, Waldemar; Jabłoński, Sławomir; Kordiak, Jacek (Archives of Medical Science, 2006)
Introduction: The role of erythropoietin (EPO) in patients with renal cysts remains unclear. Some authors suggest that EPO may be produced in renal cysts (RC). The aim of the study was to answer the question why concentration of EPO in the cystic fluid (fEPO) is higher than the serum level of EPO. Material and methods: Serum levels of EPO (sEPO) and cystic fluid levels of EPO (fEPO) were determined in a group of 33 patients (age ranging from 24 to 56 years) with renal cysts and no symptoms of either renal insufficiency or anaemia. Similar tests (excluding fEPO) were performed in the healthy controls – K (33 adults, age ranging from 26 to 53 years). Haematological parameters and serum urea (UREA) and creatinine (CREA) concentration were also determined. Results: Levels of EPO in the cystic fluid were, on the average 35 times higher than serum levels of EPO. Levels of sEPO in patients with RC were comparable to the control group C. Significantly higher urea levels, lower reticulocyte count, lower haemoglobin concentration and increased anisocytosis of the red cells were found in the study group compared to the control group. Conclusions: The study suggests that in patients with solitary renal cysts there is no erythropoietin penetration from the cyst fluid into the blood serum. The role of high erythropoietin concentration in renal cyst fluid requires further study.